Leadership Strategy of District Head Towards Employee Work Effectiveness at the District Head's Office of Ulee Kareng District - Nurliana, Nurliana; Anggela, Mutiara; Ellyana, Cut Putri (Dinasti Publisher, 2023)
Related to the Sub-district Head's Leadership Strategy on Employee Work Effectiveness at the Sub-district Head's Office in Ulee Kareng District, Employee Work Effectiveness is one of the factors that plays an important role in organizational activities that need to be fostered and developed so that organizational goals can be achieved effectively. The Sub-district Head is a sub-district government apparatus who carries out the implementation of duties in the Ulee Kareng District of Banda Aceh City who works for the community and should provide the best service for the community, but what often happens is that employees arrive late to the office at the specified time, even do not attend the morning roll call according to employee discipline standards, some even leave the office before work hours end. This is where the role and function of the sub-district head's leadership is required in managing his employees so that they can carry out their duties and responsibilities so that they can work effectively. To analyze the effectiveness of employee work at the Ulee Kareng Sub-district Head's Office, this study uses a qualitative approach method. Research that produces and processes descriptive data, such as interviews, observations, and documentation. In qualitative research, it is necessary to emphasize the importance of closeness to people in the research situation, so that researchers gain a clear understanding of the reality and conditions of life. The results of this study indicate that the leadership of the sub-district head in improving discipline, firm action is taken so that the results of employee work are in accordance with existing standards, but of course, so that the work results can be perfect, it must be supported by the creation of a good work environment, so that a reciprocal relationship is established between leaders and subordinates to complement each other according to duties and responsibilities.